Metastatic and non-metastatic melanoma imaging using Sgc8-c aptamer PTK7-recognizer - Estefanía Sicco (Nature Portfolio, 2021)
Abstract Melanoma is one of the most aggressive and deadly skin cancers, and although histopathological criteria are used for its prognosis, biomarkers are necessary to identify the different evolution stages. The applications of molecular imaging include the in vivo diagnosis of cancer with probes that recognize the tumor-biomarkers specific expression allowing external image acquisitions and evaluation of the biological process in quali-quantitative ways. Aptamers are oligonucleotides that recognize targets with high affinity and specificity presenting advantages that make them interesting molecular imaging probes. Sgc8-c (DNA-aptamer) selectively recognizes PTK7-receptor overexpressed in various types of tumors. Herein, Sgc8-c was evaluated, for the first time, in a metastatic melanoma model as molecular imaging probe for in vivo diagnostic, as well as in a non-metastatic melanoma model. Firstly, two probes, radio- and fluorescent-probe, were in vitro evaluated verifying the high specific PTK7 recognition and its internalization in tumor cells by the endosomal route. Secondly, in vivo proof of concept was performed in animal tumor models. In addition, they have rapid clearance from blood exhibiting excellent target (tumor)/non-target organ ratios. Furthermore, optimal biodistribution was observed 24 h after probes injections accumulating almost exclusively in the tumor tissue. Sgc8-c is a potential tool for their specific use in the early detection of melanoma.